Role of Neuronal Ras Activity in Adult Hippocampal Neurogenesis and Cognition - Manns, Martina; Leske, Oliver; Gottfried, Sebastian; Bichler, Zoe; Lafenetre, Pauline; Wahle, Petra; Heumann, Rolf (Frontiers in Neuroscience, 2011)
Hippocampal neurogenesis in the adult mammalian brain is modulated by various signals like growth factors, hormones, neuropeptides, and neurotransmitters. All of these factors can (but not necessarily do) converge on the activation of the G protein p21Ras. We used a transgenic mouse model (synRas mice) expressing constitutively activated G12V-Harvey Ras selectively in differentiated neurons to investigate the possible effects onto neurogenesis. Ras activation in neurons attenuates hippocampal precursor cell generation at an early stage of the proliferative cascade before neuronal lineage determination occurs. Therefore it is unlikely that the transgenically activated Ras in neurons mediates this effect by a direct, intracellular signaling mechanism. Voluntary exercise restores neurogenesis up to wild type level presumably mediated by brain derived neurotrophic factor. Reduced neurogenesis is linked to impairments in spatial short-term memory and object recognition, the latter can be rescued by voluntary exercise, as well. These data support the view that new cells significantly increase complexity that can be processed by the hippocampal network when experience requires high demands to associate stimuli over time and/or space.